SCLE and dermatomyositis in anti‐PD‐1 therapy. (1st September 2019) - Marano, A.L.; Clarke, J.M.; Morse, M.A.; Shah, A.; Barrow, W.; Selim, M.A.; Hall, R.P.; Cardones, A.R.
Summary: PD‐1 inhibitors are a relatively new type of drug that are used to treat patients with metastatic (widespread) cancers. Examples include drugs called pembrolizumab and nivolumab. Unfortunately this type of treatment can be associated with auto‐immune side effects, which means that the body's immune system, which protects against infection, wrongly attacks some parts of the body. Examples of auto‐immune side effects linked to PD‐1 inhibitors include colitis, thyroid disease and skin inflammation, including eczema‐like rashes and vitiligo. The authors of this study, based at Duke University, USA, describe two patients who developed a type of lupus called subacute cutaneous lupus erythematosus (SCLE) while on PD‐1. SCLE is an autoimmune disease. In one case, the drug that was being used, nivolumab, was discontinued; the oncologists unsuccessfully treated the patient with infliximab, a type of drug called a TNFα inhibitor, but the eruption came under control with creams and hydroxychloroquine treatment by the dermatologists. Because nivolumab was helping to treat the patient's cancer, the drug was re‐introduced but unfortunately he then developed features of another autoimmune condition, dermatomyositis, and the drug was stopped. The second patient developed SCLE following pembrolizumab treatment, which she discontinued as it was not having an effect on her cancer. Again her SCLE came under control with treatment. The authors observed that treatment with a TNF inhibitor would not be ideal in this situation, because it can itself cause lupus. Whereas SCLE is well recognised as a side effect of many drugs, it is unusual to see two different connective tissue diseases, lupus and dermatomyositis, caused by one drug. The authors advise not continuing the drug in this situation.